The Influence of Organizational Culture, Position Placement and Motivation on The Work Performance of Employees of PT. BPR Bank Bantul (Perseroda) - Gustari, Estu; Kirana, Kusuma Chandra; Subiyanto, Didik (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Organizational culture is a system of values, beliefs and habits in an organization that interact with the structure of its formal system to produce norms of organizational behavior. The purpose of this study is to partially and simultaneously determine the variables of organizational culture, position placement and motivation for the work performance of PT. BPR Bank Bantul. The method used in this study is using quantitative methods. The sempel retrieval technique used simple random sampling and obtained sempel as many as 98 employees of PT. BPR Bank Bantul. The results of this study show that the variable Organizational culture (X1) does not have a significant effect on job performance (Y). The position placement variable (X2) does not have a significant effect on job performance (Y). The motivation variable (X3) affects work performance (Y). Organizational culture, position placement and motivation simultaneously affect the work performance of PT. BPR Bank Bantul.